A novel approach for bio-lubricant production from rapeseed oil-based biodiesel using ultrasound irradiation: Multi-objective optimization. (February 2021) - Almasi, Sara; Ghobadian, Barat; Najafi, Gholamhassan; Dehghani Soufi, Masoud
Abstract: Due to the damaging environmental impacts resulting from direct entry of mineral lubricants into the environment, the use of bio-lubricants as a sustainable and renewable alternative to mineral lubricants is necessary; therefore, bio-based lubricants play an important role in overcoming existing challenges and reducing energy consumption. The present research has been conducted to intensity the production process of TMPTE (trimethylolpropane triester) from rapeseed methyl ester under the influence of ultrasonic irradiation. Ultrasound irradiation is one of the efficient and new methods to intensify the TMPTE production reaction. Ultrasound significantly intensifies the overall process with reduction in energy consumption. The response surface methodology was used for the multi-objective optimization of the process input variables in order to obtain the highest yield with the lowest energy consumption. The optimized results of this experiment reveal that with the amplitude of 82%, cycle of 40%, and reaction time of 60 min a bio-lubricant yield of 82.21% with an energy consumption of 116.7 kJ is obtained.